An Evaluation on Deep Caries Removal Method and Management Performed by Undergraduate Dental Students: A Malaysia Experience - Nurin Izyani Othman; Hanan Umaira Ismail; Muhammad Syafiq Alauddin; Norazlina Mohammad; Norzalina Ghazali (Thieme, 2024)
Indexed by Scopus